Assessment of passive knee stiffness and viscosity in individuals with spinal cord injury using pendulum test. (March 2015) - Joghtaei, Mahmoud; Arab, Amir Massoud; Hashemi-Nasl, Hamed; Joghataei, Mohammad Taghi; Tokhi, Mohammad Osman
Abstract : Objective: Stiffness and viscosity represent passive resistances to joint motion related with the structural properties of the joint tissue and of the musculotendinous complex. Both parameters can be affected in patients with spinal cord injury (SCI). The purpose of this study was to measure passive knee stiffness and viscosity in patients with SCI with paraplegia and healthy subjects using Wartenberg pendulum test. Design: Non-experimental, cross-sectional, case–control design. Setting: An outpatient physical therapy clinic, University of social welfare and Rehabilitation Science, Iran. Patients: A sample of convenience sample of 30 subjects participated in the study. Subjects were categorized into two groups: individuals with paraplegic SCI ( n  = 15, age: 34.60 ± 9.18 years) and 15 able-bodied individuals as control group ( n  = 15, age: 30.66 ± 11.13 years). Interventions: Not applicable. Main measures: Passive pendulum test of Wartenberg was used to measure passive viscous-elastic parameters of the knee (stiffness, viscosity) in all subjects. Results: Statistical analysis (independent t -test) revealed significant difference in the joint stiffness between healthy subjects and those with paraplegic SCI (P = 0.01). However, no significant difference was found in the viscosity between two groups (P = 0.17). Except for first peak flexion angle, all other displacement kinematic parameters exhibited no statistically significant difference between normal subjects and subjects with SCI. Conclusions: Patients with SCI have significantly greater joint stiffness compared to able-bodied subjects.